The Effect of Leadership Style and Work Motivation on the Performance of Truck Drivers at PT Manggala Kiat Ananda - Farady, Mochamad Adam Ilmanda; Setiono, Beni Agus; Purwiyanto, Didik (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2026)
This study aims to analyze the effect of leadership style and work motivation on the performance of truck drivers at PT Manggala Kiat Ananda, East Java area. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to truck drivers as respondents and analyzed using multiple linear regression analysis. The results indicate that partially, leadership style has a positive and significant effect on truck drivers’ performance. Meanwhile, work motivation does not have a significant partial effect on performance. However, simultaneously, leadership style and work motivation significantly influence truck drivers’ performance. These findings suggest that drivers’ performance is more strongly influenced by structural and leadership factors than by individual motivational aspects alone. In a work environment characterized by standardized procedures and strict operational regulations, effective leadership plays a crucial role in enhancing discipline, responsibility, and work compliance. This study implies that transportation companies should strengthen operational leadership capacity and manage work motivation in an integrated manner to sustain performance improvement.